Pengajian Akidah Di Institusi Pengajian Tinggi Awam (IPTA) di Malaysia: Analisis Terhadap Silibus Pengajian di UM dan UKM - Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2006)
The study of aqidah is the most significant part in the Islamic educational system, formal or informal. In Malaysia, the study began in informal traditional system especially in 'pondok institution.' In the later development, this study was introduced into the national educational system beginning from primary school to institution of higher learning. This article analyses the syllabi of aqidah in government universities in Malaysia. The analysis is focused on the undergraduate syllabi of Aqidah of the University of Malaya (UM) and the National University of Malaysia (UKM). The author uses content analysis to study whether this syllabus is relevant to our national educational system of higher learning or not by taking into consideration factors like the changing world, globalization challenges and the reality of ummah especially in Malaysia. Some recommendations are made to strengthen the content of the syllabus.